2018
DOI: 10.1088/1742-5468/aabbcf
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic measurement of the sound velocity of a Bose gas across the transition to Bose–Einstein condensation

Abstract: We present an alternative method for determining the sound velocity in atomic Bose-Einstein condensates, based on thermodynamic global variables. The total number of trapped atoms was as a function of temperature carefully studied across the phase transition, at constant volume. It allowed us to evaluate the sound velocity resulting in consistent values from the quantum to classical regime, in good agreement with previous results found in literature. We also provide some insight about the dominant sound mode (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…From a general point of view, we expect the induced interaction to decrease with increasing temperature. The reason is that the Bose gas becomes less compressible as particles are excited out of the BEC [47]. This effect will however be small for temperatures much smaller than the critical temperature of the BEC, as considered in this paper.…”
Section: A Weak Couplingmentioning
confidence: 90%
“…From a general point of view, we expect the induced interaction to decrease with increasing temperature. The reason is that the Bose gas becomes less compressible as particles are excited out of the BEC [47]. This effect will however be small for temperatures much smaller than the critical temperature of the BEC, as considered in this paper.…”
Section: A Weak Couplingmentioning
confidence: 90%
“…In harmonically trapped gases, following first studies of collisionless excitations [9][10][11], a pioneering study [12] revealed the analogs of first and second sound in two collective modes with frequencies between the hydrodynamic and collisionless predictions. Further studies have explored the effects of interactions on the first sound above T c [13,14] and on the second sound and related thermodynamics below it [15][16][17]. Recently, simultaneous observation of first and second sound has been used to characterize the superfluid transition in two dimensions (2D) [18].…”
mentioning
confidence: 99%
“…(63) In this section, we will see the measurements of this quantities and also how the global thermodynamic approach has been successes in explain the behavior of the phase transition of this system.…”
Section: Achieved Measurementsmentioning
confidence: 99%